Utilization of Digital Technology in Marketing Education Services at Kusuma Bangsa High School Palembang - Zulkipli, Zulkipli; Firmansyah, Firmansyah; Kanada, Rabial (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
This research discusses the utilization of digital technology in the context of marketing educational services at Kusuma Bangsa High School Palembang. This research is a type of qualitative research with descriptive characteristics that explores various qualitative aspects in understanding marketing strategies involving digital technology. In this study, data were obtained through interviews, observations, and documentation from various parties, including the principal, vice principal for student affairs, multimedia experts, and other resource persons who have related information. Data analysis was conducted through data reduction, data presentation, and data verification. To ensure data validity, the research used data triangulation, which includes triangulation of sources, methods and techniques. The results showed that the utilization of digital technology is an important key to the existence of educational institutions in the digital era. Kusuma Bangsa High School Palembang implements an education services marketing strategy through various digital platforms, with content curation and public relations team training. The utilization of digital technology in marketing education services at Kusuma Bangsa High School Palembang has succeeded in maintaining its existence and attracting public interest. This research provides in-depth information about the importance of digital technology in marketing education services and how educational institutions can utilize it effectively. The implications of this research are expected to be useful for other educational institutions that want to improve marketing efforts through digital technology.